2019
DOI: 10.18662/rrem/173
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Intensity Interval Training Applied with Vitamin E Reinforcement on Thyroid Hormone Metabolism

Abstract: The aim of the present research was to investigate the effect of vitamin E supplement applied with high intensity interval trainings (HIIT) on the thyroid hormone values. The research group consisted of 12 voluntary male sportsman; High intensity interval training and supplement groups (HIIT+V). HIIT group was participated only tabata model training program 3 days for 8 weeks. The HIIT+ V group was taken the vitamin e in addition to the trainings. Blood samples were taken two times from the participants in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A statistically significant increase was found in AST and ALT levels after acute exercise in 12 sedentary male subjects with a mean age of 25 [23]. Exercise is known to cause short-or longterm changes in blood biochemistry [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant increase was found in AST and ALT levels after acute exercise in 12 sedentary male subjects with a mean age of 25 [23]. Exercise is known to cause short-or longterm changes in blood biochemistry [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…HIIT programs can be carried out in all exercise styles, including cycling, walking, swimming, water training, elliptical crosstraining, and many group exercise classes. 24,25 Studies in the literature have shown that HIIT can enhance aerobic and anaerobic fitness, blood pressure, cardiovascular health, insulin sensitivity (helps exercise muscles utilize glucose for energy more easily), thyroid metabolism, 26 cholesterol profiles, muscle mass. It is thought to have positive effects on the preservation and reduction of body weight.…”
Section: What Is the High İntensive İnterval Training (Hiit) ?mentioning
confidence: 99%